Changes of intestinal microbiota and liver metabolomics in yellow catfish (Pelteobagrus fulvidraco) before and after rice flowering in rice-fish symbiosis farmed mode - Cheng, Rui; Ying, Zhuoqi; Yang, Yang; Zhang, Chongying; Zhou, Wei; Zhang, Zhiming; Ding, Huiping; Zhou, Ya; Zhang, Chi (Frontiers in Microbiology, 2025)
The rice-fish symbiosis farming model (RFFM) has been shown to enhance gut microbial diversity and improve immunity in fish. To examine changes in gut microbiota and hepatic metabolism in yellow catfish (Pelteobagrus fulvidraco) during different rice growth stages, we analyzed samples collected from the pre-flowering (Group P) and after-flowering (Group A) phases. Gut microbiota composition was assessed using 16S rRNA sequencing, with data analyzed using Principal component analysis (PCA), while hepatic metabolic profiles were characterized through untargeted metabolomics using XCMS and metaX for data processing. Our results revealed a significant increase in gut microbial diversity in Group A. Notably, the relative abundances of Pseudomonas and Cetobacterium were significantly lower in Group A compared to Group P, whereas Brevundimonas, Oxyphotobacteria_unclassified, and Clostridium_sensu_stricto_1 were more abundant in Group A. Hepatic metabolic profiles also differed between the two groups, with amino acid metabolism and related pathways being upregulated, while lipid metabolism and associated pathways were downregulated in Group A. Correlation analysis using SPSS suggested that Clostridium_sensu_stricto_1, a dominant bacterial group, played a key role in mediating hepatic metabolic changes under the RFFM. These findings indicate that rice flowering in the rice-fish symbiosis system positively influences gut microbiota composition and hepatic metabolism in yellow catfish. Furthermore, Clostridium_sensu_stricto_1 may have potential as a probiotic for improving fish health in this integrated farming system.